The spectral evolution of hot white dwarfs. Issue Volume 15:Issue S357(2019) (October 2019) - Bédard, Antoine; Bergeron, Pierre; Fontaine, Gilles
Abstract: As they evolve, white dwarfs undergo major changes in their atmospheric composition, a phenomenon known as spectral evolution. In particular, most hot He-rich (DO) stars transform into H-rich (DA) stars as they cool off, most likely as a result of the float-up of residual H. We investigate this DO-to-DA transition by taking advantage of the extensive spectroscopic dataset provided by the Sloan Digital Sky Survey (SDSS). Using our new state-of-the-art non-LTE model atmospheres, we perform a spectroscopic analysis of 1882 hot ( T eff >30, 000 K) white dwarfs identified in the SDSS. We find that at least 15% of all white dwarfs are born with a He-dominated atmosphere. Among these, ∼2/3 turn into H-rich stars before they reach T eff ∼40, 000 K, while the remaining ∼1/3 maintain their He-rich surface throughout their entire evolution. We speculate on the origin of these two groups of objects.